The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/nep.13464
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease epidemic: How do we deal with it?

Abstract: Chronic kidney disease (CKD) is a leading cause of mortality and morbidity around the world. The prevalence of CKD increases steadily over the past decade in parallel to the rapid expansion of diabetic population. Apart from increased mortality, CKD also has significant impact on quality of life and the economy. The approach to deal with the global CKD epidemic is multifaceted. Early detection by screening high‐risk individuals such as those with hypertension and diabetes is important and cost‐effective. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
56
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 40 publications
(78 reference statements)
0
56
0
2
Order By: Relevance
“…Increasing prevalence of chronic kidney disease (CKD), high costs of treating individuals with kidney failure, and poor outcomes related to renal replacement therapies are important health challenges across the globe [1]. It has been suggested, that the overall burden of CKD is largely driven by the increase in the prevalence of diabetes, mainly that of type 2 https://doi.org/10.1016/j.diabres.2019.06.016 0168-8227/Ó 2019 Published by Elsevier B.V. [2]. However CKD is a major health concern also in type 1 diabetes (T1D) as, over the course of a lifetime, diabetic nephropathy affects approximately one third of this population [3].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing prevalence of chronic kidney disease (CKD), high costs of treating individuals with kidney failure, and poor outcomes related to renal replacement therapies are important health challenges across the globe [1]. It has been suggested, that the overall burden of CKD is largely driven by the increase in the prevalence of diabetes, mainly that of type 2 https://doi.org/10.1016/j.diabres.2019.06.016 0168-8227/Ó 2019 Published by Elsevier B.V. [2]. However CKD is a major health concern also in type 1 diabetes (T1D) as, over the course of a lifetime, diabetic nephropathy affects approximately one third of this population [3].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of chronic kidney disease (CKD) has risen significantly during the last several decades, and it is now a major public health issue that poses enormous economic challenges worldwide (1). According to recent epidemiological surveys, more than 500 million people worldwide currently have some stage of CKD (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Delaying the development of CKD is critical. Studies have found that using RAS inhibitors and controlling salt levels, blood pressure, and blood lipid levels can effectively delay the development of CKD, providing the direction for the development of speci c therapeutic drugs [1,6]. In recent years, the replacement therapy of CKD brosis by natural products has attracted the attention of many scholars [7].…”
Section: Introductionmentioning
confidence: 99%